Nonionic Surfactant-Assisted In Situ Generation of Stable Passivation Protective Layer for Highly Stable Aqueous Zn Metal Anodes - Zhang, Yuanjun; Zheng, Xiaoyang; Wu, Kuan; Zhang, Ying; Xu, Gang; Wu, Minghong; Liu, Hua-Kun; Dou, Shi-Xue; Wu, Chao (Nano letters, 2022)
A highly stable interface for aqueous rechargeable Zn batteries is of importance to inhibit the growth of Zn dendrites and suppress the side reactions. In this work, we have developed a stable honeycomb-like ZnO passivation protective layer on the Zn surface, which is in situ generated with the assistance of a nonionic surfactant additive (polyethylene glycol tert-octylphenyl ether, denoted as PEGTE). The ZnO passivation layer can facilitate the uniform distribution of the electric field, guiding the uniform deposition of Zn2+ and inhibit the generation of dendrites. As a result, the symmetric cell using the electrolyte with PEGTE shows an excellent performance at high areal capacity, reflected by stable cycling for over 2400 h at 5 mAh/cm2 and 1300 h at 10 mAh/cm2. The full cell paired with V2O5 demonstrates a long lifespan for more than 600 cycles at a low negative/positive capacity ratio.